Performance assessment of an advanced triple-cycle system based upon solid oxide fuel cells, vacuum thermionic generators and absorption refrigerators. (1st August 2019) - Zhang, Houcheng; Wang, Jiatang; Wang, Fu; Zhao, Jiapei; Miao, He; Yuan, Jinliang
Highlights: An advanced triple-cycle system is proposed for waste heat recovery. Various irreversible losses within the system are mathematically described. Maximum power density and its efficiency are increased by 20.3% and 18.4%. Effects of some important parameters on system performance are revealed. Effects of microstructure parameters and operating conditions are discussed. Abstract: In addition to generate electricity, solid oxide fuel cells also produce a considerable quantity of high-quality waste heat. To harvest the waste heat, an advanced triple-cycle system based upon solid oxide fuel cells, vacuum thermionic generators and absorption refrigerators is theoretically put forward. Assuming that the main irreversible losses within the system are thermodynamic and electrochemical losses, the performance parameters mathematically evaluating the whole system are specified under different operating conditions. The effectiveness is also demonstrated through performance comparisons between the proposed system and the stand-alone solid oxide fuel cell system. Numerical calculations show that the maximum attainable power density and its corresponding efficiency allow 20.3% and 18.4% larger than that of the stand-alone solid oxide fuel cell system, respectively. Comprehensive parametric studies are further undertaken to reveal the influences of some decisive design parameters and operating conditions on the triple-cycle system performance. Results show that the microstructure parameters of the solid oxide fuel cell and the anode temperature of the vacuum thermionic generator can be optimally designed to maximize the power density of the triple-cycle system. The vacuum thermionic generator can be treated as the alternative intermediate cycle for SOFC based triple-cycle systems.